التحليل الصرفي في تعليم اللغة العربية: دراسة في البنية والدلالة - Muqit, Abdul (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2025)
This study explores the field of Arabic morphology by examining the structural and semantic dimensions of word formation. Morphology, as a core component of Arabic linguistics, investigates the patterns and transformations of words, focusing on roots, weights, and derivational structures. The research adopts a descriptive-analytical methodology, utilizing classical texts such as the Qur’an, Hadith, and Arabic literature, alongside modern linguistic corpora and natural language processing (NLP) tools. The findings reveal that Arabic morphology exhibits a high degree of derivational flexibility, with consistent semantic functions linked to morphological patterns. The study highlights the effectiveness of digital tools in identifying complex morphological structures and underscores the need for standardized morphological databases to support computational linguistics applications. Additionally, it uncovers gaps in educational practices and student awareness of morphological nuances. By integrating traditional linguistic theories with modern computational approaches, the research proposes a unified analytical framework for both pedagogical and technological advancement. It concludes that Arabic morphology remains essential not only for linguistic analysis but also for modern applications in education, artificial intelligence, and digital content development.